New Persian cooking : a fresh approach to the classic cuisine of Iran / Jila Dana-Haeri, Shahrzad Ghorashian ; Photography by Jason Lowe - Dana-Haeri, Jila
The subtleties of Persian cuisine and their exciting mix of flavours are totally distinct from other styles of cooking and make it one of the great cuisines of the world. The traditional emphasis on the use of fresh and seasonal ingredients and the importance of a complementary mix of herbs, vegetables, meat, fish, fruit and spices, accords well with the modern desire for healthy eating and a balanced diet. This highly-illustrated cookbook offers an enticing introduction to traditional Persian cuisine through recipes that are accessible to the non-professional cook and are based on ingredients.